The Principles of Environmental Based Development in International Law and Sustainable Development Goals - Sandy Kurnia Christmas; Aminah Aminah (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The Sustainable Development Goals or SDGs are development goals in 2030 to carry out environmentally sound development, which explicitly aims to carry out development that is to meet environmental sustainability and is based on human rights. It is also an adaptation of the principles of the Stockholm Declaration 1972.Purpose/Objective Study: This research is to find the principles of environmentally sound development, both within the principles of international law and the SDGs principles, that are expected in future development policies to be carried out in the perspective of the right to the environment, both the central and regional governments.Design/Methodology/Approach: In this doctrinal law research, it is examined using the conceptual approach contained in the principles of development and environmental principles contained in the substance of international law.Findings: In the principles of international law, there are seven principles of sustainable development goals agreed by the international community in the Rio Conference as a guideline in implementing equitable development based on human rights, which also must be guided by the targets of sustainable development within the SDGs.Paper Type: Research Article